Experiences of older people dying in nursing homes: a narrative systematic review of qualitative studies. Issue 6 (4th June 2018) - Greenwood, Nan; Menzies-Gow, Emma; Nilsson, David; Aubrey, Dawn; Emery, Claire L; Richardson, Angela
Abstract : Objectives: To identify and synthesise qualitative research from 2001 investigating older people's (65+ years) experiences of dying in nursing and care homes. Methods and outcomes: Eight electronic databases (AMED, ASSIA, CINAHL Plus, Embase, HMIC, Medline, PsychINFO and Scopus) from 2001 to July 2017 were searched. Studies were included if they were qualitative, primary research and described the experiences of dying in nursing or care homes from the perspectives of the older people themselves, their families or staff. Study quality assessment was undertaken to systematically assess methodological quality, but no studies were excluded as a result. Results: 1305 articles were identified. Nine met the inclusion criteria. North American studies dominated. Most used a mixture of observations and interviews. All the included studies highlighted the physical discomfort of dying, with many older people experiencing potentially avoidable symptoms if care were to be improved. Negative psychosocial experiences such as loneliness and depression were also often described in addition to limited support with spiritual needs. Conclusions: More qualitative research giving a holistic understanding of older people's experiences of dying in residential care homes is needed. Undertaking research on this topic is challenging and requires great sensitivity, but the dearth of qualitative research from the perspectives of those most closely involved in older people's deaths hampers service improvement.